Changes in VEGF level and tumor growth characteristics during lewis lung carcinoma progression towards CIS-DDP resistance - Pyaskovskaya, O.N.; Dasyukevich, O.I.; Kolesnik, D.L.; Garmanchouk, L.V.; Todor, I.N.; Solyanik, G.I. (Experimental Oncology, 2007)
Aim: To study the relationship between tumor angiogenic potential and its growth and metastasis using Lewis lung carcinoma (LLC) models with different degree of resistance to cis-diamminedichloroplatinum (cis-DDP). Methods: LLC and its two cis-DDP-resistant variants (LLC-9 и LLC-19), were used. For determination of angiogenic potential of LLC, LLC-9 and LLC-19, the level of VEGF production by these tumor cells in vitro and the level of circulating VEGF during tumor growth in vivo was measured by enzyme-linked immunosorbent assay. Results: Progressive decrease of LLC-9 and LLC-19 sensitivity to action of cis-DDP evidenced in vitro (IC50 = 0.0077 ± 0.0005 mg/ml and 0.0156 ± 0.0008 mg/ml respectively vs. 0.004 ± 0.0003 mg/ml for LLC, p < 0.05) and in vivo (index of primary tumor growth inhibition by cis-DDP was 26% and 3% respectively vs. 46%; index of metastasis inhibition — 46% and 11% vs. 65%, p < 0.05) was accompanied by the significant changes of tumor angiogenic potential. The level of VEGF production by primary culture of LLC-9 in vitro was 1.5 fold higher (p < 0.05) than that by primary culture of LLC, whereas there were no differences in the level of VEGF production between LLC-19 and LLC. The level of circulating VEGF drastically increased in the initial phase of LLC-9 and LLC-19 growth in vivo, whereas in LLC bearing mice the dynamic changes of VEGF level are characterized by the presence of long-term latent period (tlag = 17.0 ± 0.3 days). In LLC bearing mice the character of changes of circulating VEGF level significantly correlated with the number of metastases (p < 0.001) but not with tumor volume; while in LLC-9 bearing mice — with tumor volume (p < 0.01) and the number of metastases (p < 0.05). Although maximum level of circulating VEGF was significantly (p < 0.05) higher in LLC-9 bearing mice than that in LLC bearing mice, maximum number of lung metastases was significantly (p < 0.05) lower in LLC-9 bearing mice vs LLC. In contrast to LLC-9, in LLC-19 bearing mice the level of metastatic injury was significantly elevated (p < 0.05) and the level of circulating VEGF considerably correlated with both tumor volume (p < 0.01) and metastatic index (p < 0.01). Conclusion: There is revealed a direct correlation between the level of circulating VEGF and all parameters of tumor progression observed only in the cases of highly resistant tumors, whilst elevation of circulating VEGF level during tumor growth in vivo could be considered as a marker of metastasis not dependent on a drug resistance of tumor. Цель: изучить взаимосвязь между ангиогенным потенциалом опухоли и распространенностью опухолевого процесса на модели карциномы Льюис разной степени резистентности к действию cis-DDP. Методы: в работе использовали карциному легкого Льюис (LLC), а также два ее варианта (LLC-9 и LLC-19), полученные на 9-м и 19-м этапе экспериментальной прогрессии LLC в направлении формирования резистентности к cis-DDP in vivo. Ангиогенный потенциал LLC, LLC-9 и LLC-19 оценивали иммуноферментным методом по уровню продукции VEGF первичными культурами in vitro, а также по динамике изменений уровня циркулирующего VEGF в процессе роста LLC in vivo. Результаты: прогрессивное снижение чувствительности LLC-9 и LLC-19 к действию cis-DDP, подтверждавееся in vitro ( 50 = 0,0077 ± 0,0005 мг/мл для LLC-9 и 0,0156 ± 0,0008 мг/мл для LLC-19 против 0,004 ± 0,0003 мг/мл для LLC, p < 0,05) и in vivo (индекс торможения цитостатиком роста LLC-9 и LLC-19 cоставлял 26 и 3% соответственно против 46% для LLC; метастазирования — 46 и 11% против 65% для LLC, p < 0,05), сопровождалось значительными изменениями ее ангиогенного потенциала. Уровень продукции in vitro n vitro первичной культурой LLC-9 был в 1,5 раза выше (p < 0,05) по сравнению с таковым первичной культурой LLC, тогда как уровень продукции VEGF первичной культурой LLC-19 практически не отличался от такового для LLC. У ровень циркулирующего VEGF резко повышался уже на ранних этапах роста LLC-9 и LLC-19 in vivo, тогда как у мышей с LLC динамика изменения его уровня характеризовалась длительным латентным периодом (tlag = 17,0 ± 0,3 сут). Характер изменений уровня циркулирующего VEGF в процессе роста LLC (p < 0,001) коррелировал с количеством метастазов; у животных с LLC-9 — с объемом опухоли (p < 0,01) и количеством (p < 0,05) метастазов. Несмотря на то, что максимальный уровень циркулирующего VEGF у мышей с LLC-9 значительно (p < 0,05) выше, чем у мышей с LLC, максимальное количество метастазов в легких у мышей с LLC-9 достоверно (p < 0,05) меньше, чем у мышей с LLC. В отличие от LLC-9, в процессе роста LLC-19, сопровождавшегося повышением уровня метастатического поражения легких p < 0,05), уровень циркулирующего VEGF коррелировал как с объемом опухоли (p < 0.01), так и с исследованными показателями метастазирования (p 0.01). Выводы: прямую корреляционную взаимосвязь между уровнем циркулирующего VEGF и изученными показателями распространенности опухолевого процесса выявляют лишь для опухолей с высокой степенью лекарственной резистентности, тогда как повышение уровня циркулирующего VEGF в процессе роста опухоли можно рассматривать в качестве маркера имеющихся метастазов независимо от степени ее резистентности.